2022
DOI: 10.18502/aoh.v6i1.8665
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Estimating the 3 kHz Audiometric Threshold by Averaging the Thresholds at 2 and 4 kHz in Cases of Noise-Induced Hearing Loss

Abstract: Background: Hearing thresholds at 3000 Hz are generally not measured in routine clinical audiometry. However, for purposes other than clinical diagnosis, the threshold at 3 kHz has many applications, in epidemiological studies in the field of occupational health and medicine, as well as in (medicolegal) quantification of physical impairment due to hearing loss, particularly noise-induced hearing loss (NIHL). The present study addressed the validity of estimating, in the case of NIHL, the 3 kHz-audiometric thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It has been shown that, for epidemiological studies involving large amounts of data, the interpolated threshold may be considered as a valid estimate of the true value of the 3 kHz threshold. 33 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that, for epidemiological studies involving large amounts of data, the interpolated threshold may be considered as a valid estimate of the true value of the 3 kHz threshold. 33 …”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that, for epidemiological studies involving large amounts of data, the interpolated threshold may be considered as a valid estimate of the true value of the 3 kHz threshold. 33 For CERA, a Bio-Logic Navigator PRO system (Bio-logic Systems Corp. Orlando, FL, USA) was used, with the following parameters: stimulus 50 milliseconds tone-burst, 1 / s; filtering 0,1 to 10 Hz; analysis epoch: 600 milliseconds; # stimuli: 50 to 250. Then, CERA responses were recorded four times at each intensity level.…”
Section: Design and Protocolmentioning
confidence: 99%
“…The plots show a good agreement, without either a proportional error (difference increasing with average value) or a variation that strongly depends on the magnitude of the measurements. The validity of estimating the 3 kHz audiometric threshold by averaging the thresholds at 2 and 4 kHz in cases of noise-induced hearing loss is discussed in a previous publication [18].…”
Section: Resultsmentioning
confidence: 99%